Strategy for the Development of Kuranding Lake Tourist Attraction in Tanjung Beringin Village, South Bengkulu Regency - Indarti, Sri; Mimi Julilah; Rosidin (GAYAKU PUBLISHER, 2024)
Indonesia is an archipelago that has many good and beautiful places, including mountains, green nature, rivers and more. This is utilized as a tourist attraction that adds to the income of the tourist attraction area, one of the tours is Kuranding Lake, this tour is located in Tanjung Beringin Village, Air Nipis Subdistrict, South Bengkulu Regency, Kuranding Lake Tourism is relatively new and there are still many who do not know about this tour. The problem in this study is how the development strategy of the Kuranding lake tourist attraction in Tanjung Beringin Village, South Bengkulu Regency, The purpose of this study is to describe the development strategy carried out by the management or manager of the Kuranding lake tourist attraction. This research uses descriptive qualitative methods, collection techniques by means of observation, interviews, and documentation. The data analysis technique used is an interactive analysis technique consisting of three components, namely data reduction, data presentation, and conclusion drawing. From the results of the study according to the research focus, the dimensions of the strategy are objectives, policies and programs, there are 6 short-term goals and 3 medium-term goals obtained from interviews with managers, besides that there are policies for managing Kuranding lake, namely 6 policies that have been applied to Kuranding lake objects, as for several programs for Kuranding lake objects by managers, namely real or real programs, besides that there are also 3 programs as material for developing Kuranding lake tourism objects including marketing programs, lake tourism destinations, partnerships. The obstacles faced include lack of funds and need a touch from the government or other private parties. Kuranding Lake also has several resident resources such as tourist sites and environmental conditions that are still beautiful.